Pengaruh Penggunaan Model Pembelajaran Group Investigasi Bermedia dan Motivasi Belajar Siswa terhadap Pemahaman Konsep Biologi - Ratih Kumala Dewi; Asrial Asrial; Bambang Hariyadi (Universitas Jambi, 2015)
Research was conducted to determine the effect of group learning model investigations and motivation of student to the understanding of biological in class XI science SMA 12 merangintotaling 56 people. The study design consisted of two group: the experiment group and the control group as well as the intruments used were questionnaires and objective test. The result showed that: (1) there is no effect of the use of group learning model of media investigation of students understanding of concepts in biology subject. 2) thereis no difference in the ability of undestanding the concept of highly motivated students when compared to studentswho have motivation the subject of biology. 3) there is no interaction between the use of media investigative group learning model with student motivation.